Genetic Variation in the Agro-morphological Traits of Elephant Foot Yam (Amorphophallus paeoniifolius) - Ashish, Narayan; R. S., Singh; G. S., Giri; R., Prasad; P. P., Singh (JOURNAL OF ROOT CROPS, 2020)
An experiment was conducted using 21 germplasm of Elephant foot yam including one national check to find out genetic divergence among the collected genotypes. The experiment was carried out at T.C.A., Dholi Research Farm of Dr. R.P.C.A.U., Pusa, Samastipur, Bihar, in a completely Randomized Block Design with two replications during 2018. Data were collected for ten characters viz., days to sprouting, pseudostem length (cm), pseudostem girth (cm), leaf canopy diameter (cm), chlorophyll content (SPAD value), calcium oxalate (mg/100gm), dry matter (%), days to maturity, no. of cormels per plant and corm weight per plant (kg.). Analysis of variance revealed highly significant differences among the germplasm for all the ten characters under study. Maximum range was found for the characters like pseudostem length followed by leaf canopy diameter, days to sprouting, days to maturity, chlorophyll content, pseudostem girth and no. of cormels per plant. The phenotypic coefficient of variance was greater than genotypic coefficient of variance for all the characters under study and high magnitude of phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) were observed for traits like no. of cormels per plant followed by corm weight per plant, pseudostem length, days to sprouting, pseudostem girth, calcium oxalate, chlorophyll content and leaf canopy diameter indicating that these traits could be used for corm yield improvement. High estimates of heritability coupled with high genetic advance expressed as percentage of mean were observed for characters like days to sprouting, pseudostem length, pseudostem girth, leaf canopy diameter, chlorophyll content, calcium oxalate, no. of cormels per plant and corm weight per plant indicating effectiveness of selection due to preponderance of additive gene action for these traits and direct selection may be effective.